Sutures versus staples for skin closure in orthopaedic surgery: meta-analysis. (16th March 2010) - Smith, Toby O; Sexton, Debbie; Mann, Charles; Donell, Simon
Abstract : Objective To compare the clinical outcomes of staples versus sutures in wound closure after orthopaedic surgery. Design Meta-analysis. Data sources Medline, CINAHL, AMED, Embase, Scopus, and the Cochrane Library databases were searched, in addition to the grey literature, in all languages from 1950 to September 2009. Additional studies were identified from cited references. Selection criteria Two authors independently assessed papers for eligibility. Included studies were randomised and non-randomised controlled trials that compared the use of staples with suture material for wound closure after orthopaedic surgery procedures. All studies were included, and publications were not excluded because of poor methodological quality. Review methods Two authors independently reviewed studies for methodological quality and extracted data from each paper. Final data for analysis were collated through consensus. The primary outcome measure was the assessment of superficial wound infection after wound closure with staples compared with sutures. Relative risk and mean difference with 95% confidence intervals were calculated and pooled with a random effects model. Heterogeneity was assessed with I 2 and χ 2 statistical test. Results Six papers, which included 683 wounds, were identified; 332 patients underwent suture closure and 351 staple closure. The risk of developing a superficial wound infection after orthopaedic procedures was over three times greater after staple closure than suture closure (relative risk 3.83, 95% confidence interval 1.38 to 10.68; P=0.01). On subgroup analysis of hip surgery alone, the risk of developing a wound infection was four times greater after staple closure than suture closure (4.79, 1.24 to 18.47; P=0.02). There was no significant difference between sutures and staples in the development of inflammation, discharge, dehiscence, necrosis, and allergic reaction. The included studies had several major methodological limitations, including the recruitment of small, underpowered cohorts, poorly randomising patients, and not blinding assessors to the allocated methods of wound closure. Only one study had acceptable methodological quality. Conclusions After orthopaedic surgery, there is a significantly higher risk of developing a wound infection when the wound is closed with staples rather than sutures. This risk is specifically greater in patients who undergo hip surgery. The use of staples for closing hip or knee surgery wounds after orthopaedic procedures cannot be recommended, though the evidence comes from studies with substantial methodological limitations. Though we advise orthopaedic surgeons to reconsider their use of staples for wound closure, definitive randomised trials are still needed to assess this research question.